Kraven's last hunt - Kleid, Neil (Spider-Man, 2019)
"After years of crushing defeats, Kraven the Hunter--son of Russian aristocrats, game tracker supreme--launches a final, deadly assault on Peter Parker, the Amazing Spider-Man. But for the obsessed Kraven, killing his prey is not enough. Once his enemy is dead, Kraven must become the Spider."--